Providing preoperative information for children undergoing surgery: a randomized study testing different types of educational material to reduce children’s preoperative worries - Fernandes, S. C.; Arriaga, P.; Esteves, F. (Health Education Research, 2014)
This study developed three types of educational preoperative materials and examined their efficacy in preparing children for surgery by analysing children's preoperative worries and parental anxiety. The sample was recruited from three hospitals in Lisbon and consisted of 125 children, aged 8-12 years, scheduled to undergo outpatient surgery. The participants were randomly assigned to one of the seven independent conditions that were combined into the following three main groups: an experimental group, which received educational materials with information about surgery and hospitalization (a board game, a video or a booklet); a comparison group, which received entertaining material with the same format type; and a control group, which did not receive any material. Children's preoperative worries and parental anxiety were evaluated after the experimental manipulation. Children who received educational materials were significantly less worried about surgery and hospital procedures than children in the comparison and the control groups, although no statistically differences were found between the type of materials within the experimental group, and no significant effect occurred on parental state anxiety. These results do however support the hypothesis that providing preoperative materials with educational information reduce children's preoperative worries.